Response to Growth and Production of Oyster Mushrooms (Pleurotus ostreatus) with The Addition of Bran and Some Molasses Concentrations in Baglogs - Retno Sulistiyowati; Aprilia Hartanti; Ahmad Bahaudin (Universitas Muhammadiyah Sidoarjo, 2022)
Traditionally, oyster mushroom cultivation uses a simple method, namely by utilizing wood sawdust that have undergone weathering as a planting medium (baglog). To support the growth and production of oyster mushrooms, need add nutrients such as rice bran and molasses to baglogs. This study aims to determine the growth and production of oyster mushroom plants by adding bran and molasses to baglogs. Based on the results of the study, the following conclusions are: 1) the addition of bran 20% per baglog gives the best results on the volume of mycelium, the diameter of the fruit hood, and the wet weight of the fruit, 2) the concentration of molasses does not affect all parameters and 3) the interaction of adding bran 30% per baglog with a molasses concentration of 360 cc per dough on the speed of appearance of pinheads and the wet weight of the fruit.